CUFFLESS CONTINUOUS BLOOD PRESSURE PROTOTYPE USING PTT AND PIR WITH PPG AND ECG BASED - HIMAWAN KUSUMAH - NIM: 23215018, ILMAN
Blood pressure as a property of the body is one of the physiological signals that can arise spontaneously. Blood pressure is defined as the pressure of blood flow to the vessel wall. Blood pressure changes are significant and prolonged have implications for various diseases, especially cardiovascular disease and high blood pressure. It is well known that high blood pressure is one of the biggest risk factors for death in the world. Globally, the blood pressure increase by 22% to people aged up to 18 years in 2014. Continuous blood pressure monitoring as a vital sign in a person as a user becomes important so the preventive measures, early detection of disease, and further treatment be more quick and effective. Conventional monitoring of continuous blood pressure changes in patients performed by auscultatory and oscillometric measurement techniques with regular time intervals. It has limitations on the naturality and discomfort of patients because repeat arm pumping. The aim of the study is to solve the problems to determine the method of measure blood pressure that monitored continuously, cuffless, wearable and ambulatory measurement features and have the accuracy of clinical standard measurements. In this research, the design of blood pressure measurement device use method of PTT and PIR measurement. The implementation stage, the configurations use PPG and 1 lead ECG sensors to obtain PTT and PIR parameter. it obtains the value of systolic and diastolic blood pressure. The testing stage, the accuracy of blood pressure values was tested using clinical standard criteria and regression analysis to compare the measurement of blood pressure estimation from a prototype and blood pressure reference from an oscillometric for comparison. The test is performed on 40 healthy subjects in seated, stand and lying down position. The result of the purposed method is the prototype had meanÃ‚Â±standard deviation (SD) to estimate systolic, diastolic and pulse pressure were Ã‚Â0.55Ã‚Â±7.42 mmHg, Ã‚Â0.37Ã‚Â±7.20mmHg, 0.08Ã‚Â±10.07mmHg respectively. Mean absolute difference (MAD) of systole, diastole and pulse pressure were 6.02 mmHg, 6.00 mmHg, and 8.03 mmHg respectively. The correlation between estimated blood pressure and reference blood pressure has the highest R-square reach 0.719. The result of regression analysis for each subject between PTT and pulse pressure with highest R-square is 0,8943 and between PIR and diastole is 0,6637.